Consumer Confidence Index (CCI) for European countries - relation to objective household financial situation - Malgorzata Grzywińska-Rąpca; Aneta Ptak - Chmielewska (Journal of Modern Science)
Objectives The Consumer Confidence Index (CCI) has been constructed in order to measure consumer attitudes. Its construction takes into account not only the assessment of the current financial and economic situation in the country and the current level of savings, but also the expectations of consumers with regard to the above-mentioned areas of life and the management of financial resources. The objectives of the article are (1) to test and select the components contributing to the consumer confidence index by proposing a new approach to its calculation and (2) to test the links between consumer sentiment and the level of financial instruments held by European households.